(untitled) (Revista de Ciências Agroveterinárias, 2023)
The increase in plant-1 bud load can be an alternative to improve the vegeto-productive balance of the vine, however, by providing greater density of the vegetative canopy, it can result in a reduction in the chlorophyll content in the leaves. In view of this, the objective is to evaluate the chlorophyll content in leaves as a function of the increase in bud load in the ’Sauvignon Blanc’ vine grown in an altitude region of Santa Catarina. The present work was carried out during two agricultural seasons, 2017 and 2018, in the municipality of São Joaquim - SC. Sauvignon Blanc vine plants were used, grafted onto ’Paulsen 1103’. The treatments consisted of four different levels of bud loads: 15, 30, 50 and 75 buds plant-1. The chlorophyll content of the leaves was evaluated as a function of the bud load at different phenological stages, separate inflorescence, full bloom, lead grain, pea grain, turn and color and harvest, using the SPAD-502 equipment. The increase in the bud load did not influence the chlorophyll contents in different phenological stages evaluated, only in the pea grain phenological stage it was observed that the increase in the bud load resulted in an increase in the chlorophyll contents in the leaves of the ’Sauvignon Blanc’ vine, during the 2017 harvest, with no effect on the 2018 harvest.. Regarding the temporal monitoring, it is concluded that the chlorophyll contents increase until the phenological stage grain pea, with a decrease in their values in the verison, with a new increase occurring until the moment of the harvest.